Novel nematic and glassy liquid crystalline oligomers as electroluminescent organic semiconductors. Issue 5 (9th April 2021) - Hu, Guang; Kelly, Stephen M.; Kitney, Stuart P.; Harrison, William; Lambert, Brian
ABSTRACT: Several oligomers (MWs > 1000 g mol −1 ) with highly rigid and conjugated aromatic cores, incorporating 1, 4-disubstituted phenylene, 2, 7-disubstituted fluorene, 1, 4-disubstituted thiophene and/or 2, 7-disubstituted carbazole rings with lateral and terminal substituents were synthesised as novel organic semiconductors. These novel liquid crystalline oligomers exhibit glass transition temperatures above room temperature, high clearing points and a broad nematic temperature range as well as electroluminescent behaviour in solution-processed devices. Abstract :